Fractured Militancy : Precarious Resistance in South Africa after Racial Inclusion - Paret, Marcel (Book collections on Project MUSE., 2022)
"This book examines the consequences of democratization and racial inclusion in South Africa through a study of local protest and collective organizing in four low-income and predominantly Black residential areas around Johannesburg"--